Art Spiegelman : de l’outrenoir à l’outrebiographie dans In the Shadow of No Towers - Yves DAVO (E-REA)
After a study comparing Art Spiegelman’s cover album with the “outrenoir” concept theorized by the French painter Pierre Soulages, this article will aim at redefining Spiegelman’s autobiography as “outrebiography,” understood here as going beyond the bounds of a mere testimony of the self towards the biography of a shared experience. This narrative figure, at the junction of self-centered discourse and political lampoon, gives the album a dissident overtone and will thus be analyzed as a counter-narrative. The “beyond black” cover of that post-9/11 narration will eventually appear not only as revelation but as a way to resist.